1979
DOI: 10.1029/ja084ia07p03327
|View full text |Cite
|
Sign up to set email alerts
|

The effect of energetically produced O2+ on the ion temperatures of the Martian thermosphere

Abstract: In the Martian ionosphere the dominant solar ionization products are O+ and CO2+. These ions are rapidly converted to O2+ by ion neutral reactions resulting in O2+ as the dominant ion. As O2+ has a lower ionization potential, each reaction results in approximately 1.2 eV of energy to be shared by the reaction products. The kinetic energy given to the O2+ will affect the ion temperatures. Calculations have been made of the ion heating rates and temperatures which result from the degradation of these energetic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

1991
1991
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(48 citation statements)
references
References 40 publications
2
46
0
Order By: Relevance
“…This behavior approximates the ion temperatures measured by the RPA on Viking, as presented by Hanson et al (1977). The assumed electron temperature profile is similar to that calculated by Rohrbaugh et al (1979). These assumptions are sufficient for our MT-GCM simulations, since the relevant recombination rates and charge exchange reactions affecting dayside photochemical ions (below 200 km) are only weakly temperature dependent.…”
Section: Mtgcm Input Parameters For October 1999supporting
confidence: 75%
“…This behavior approximates the ion temperatures measured by the RPA on Viking, as presented by Hanson et al (1977). The assumed electron temperature profile is similar to that calculated by Rohrbaugh et al (1979). These assumptions are sufficient for our MT-GCM simulations, since the relevant recombination rates and charge exchange reactions affecting dayside photochemical ions (below 200 km) are only weakly temperature dependent.…”
Section: Mtgcm Input Parameters For October 1999supporting
confidence: 75%
“…(1) depends on the electronic temperature, which is not calculated in the LMD-MGCM. Electron temperature model used in this study depends only on the altitude, which is based on the observation by Viking (Hanson and Mantas, 1988) and calculation by Rohrbaugh et al (1979) below 200 km, as also referred by Kim et al (1998).…”
Section: Non-thermal Exospheric Componentmentioning
confidence: 99%
“…The same model indicated that energy inputs into the ion and electron gases were required at the upper boundary (again presumably associated with the solar wind interaction) in order to obtain agreement with measurements. Other work on the ionospheric energetics has also invoked either energy inputs and/or ionospheric thermal conductivities altered by ionospheric magnetic fields which are induced by the solar wind interaction (see Figure 5.3) (Rohrbaugh et al, 1979;Choi et al, 1998). For example, in the absence of magnetic field effects an input flux of 4 x 10 9 eV cm-2 s-1 is needed for the electrons (Choi et al, 1998).…”
Section: Ionosphere Modelsmentioning
confidence: 99%